Euthanasia and advanced medical directives in the perspective of ethical, moral, religious and legal issues in Malaysia and under common law - Marina Syazana Kamalruzaman,; Nurul Izzah Jafri,; David Bakit Anak Nuing, (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2022)
Whereas the medical industry has advanced significantly in recent years, there is still much debates around the subject on the legalization of euthanasia and advanced medical directives (‘AMD’). The uncertainty circulates around four different aspects which are ethical, moral, religious and legal. Especially in Malaysia which the nation consists of multicultural and multiracial with diverse beliefs and religions thus, every of those aspects need to be considered thoroughly. This study aims to depict the historical background of euthanasia and AMD which subsequently, in this study will critically analyses the ethical and moral issue arising from euthanasia and AMD based on philosophical thoughts from different school of thoughts. To understand further, this study also aims to study the religious issues based on different religions that arising from euthanasia and AMD. In another aspect, this study will examine the legal issues arising from euthanasia and AMD and suggest the appropriate legal mechanism through critical analysis. This study is conducted by using doctrinal legal research and comparative methods between jurists' opinions, various religions and comparison between Malaysia and Common Law countries. As a result from this study, it is found that euthanasia and AMD are still not widely accepted in the society and still debatable as a whole. Different opinions between various perspectives such as cultures, beliefs, political and society does influence the acceptance of euthanasia and AMD in the society. While in some Common Law countries, euthanasia is legalized as it is needed to end the person’s suffering however in Malaysia, euthanasia is not acceptable as it is related to mercy killing and murder. Therefore, the government need to work alongside with doctors or medical experts by taking account the various aspects in creating a legal framework that is justifiable and fair to the nation in order to legalize euthanasia and AMD in the country.